Effectivity Test of n-Hexane, Ethyl Acetate, and Butanol Fractions of Mango Peel (Mangifera indica L.) Gedong Gincu Variety on the Growth of Escherichia coli - Siskanti, Alvina; Brajawikalpa, Rama Samara; Apriyanto, Dadan Ramadhan (GHMJ (Global Health Management Journal), 2025)
Background: Escherichia coli was the most common cause of diarrhea. Diarrhea reached a high prevalent in West Java. The cause of antibiotic resistance to Escherichia coli was noncompliance medication. Mango peel (Mangifera indica L.) of the Gedong Gincu variety had secondary metabolites compound which act as antibacterial that can be used as alternative medication. Aims: To analyze phytochemicals and determine effectiveness of n-hexane, ethyl acetate, and butanol fractions of mango peel Gedong Gincu variety in the growth of Escherichia coli. Methods: This study used laboratory true experimental research with post-test only control group design. This research consisted 14 groups, divided into 2 control groups, namely control (+) given ciprofloxacin and control (-) given 10% DMSO, and 12 treatment groups given n-hexane, ethyl acetate, and butanol fractions concentration of Gedong Gincu 6.25%v/v, 12.5% v/v, 25% v/v, and 50% v/v. The test used well diffusion method on Mueller-Hinton Agar media. Results: The secondary metabolites in the n-hexane fraction included alkaloids, steroids, and saponins, while ethyl acetate and butanol fractions contained flavonoids, phenols, alkaloids, triterpenoids, and tannins. The results of the oneway ANOVA test obtained p<0.001 which indicated n-hexane, ethyl acetate, and butanol fractions were significantly inhibit the growth of Escherichia coli with the greatest mean inhibitory zones of 6.86 mm, 12.08 mm, and 9.35 mm, respectively. Conclusion: The most effective fraction of mango peel (Mangifera indica L.) Gedong Gincu variety in inhibit the growth of Escherichia coli was ethyl acetate fraction at a 50% concentration (12.08 mm).